New Trypanosoma evansi Type B Isolates from Ethiopian Dromedary Camels. - Hadush Birhanu; Tadesse Gebrehiwot; Bruno Maria Goddeeris; Philippe Büscher; Nick Van Reet (PLoS Neglected Tropical Diseases, 2016)
BACKGROUND:Trypanosoma (T.) evansi is a dyskinetoplastic variant of T. brucei that has gained the ability to be transmitted by all sorts of biting flies. T. evansi can be divided into type A, which is the most abundant and found in Africa, Asia and Latin America and type B, which has so far been isolated only from Kenyan dromedary camels. This study aimed at the isolation and the genetic and phenotypic characterisation of type A and B T. evansi stocks from camels in Northern Ethiopia. METHODOLOGY/PRINCIPAL FINDINGS:T. evansi was isolated in mice by inoculation with the cryopreserved buffy coat of parasitologically confirmed animals. Fourteen stocks were thus isolated and subject to genotyping with PCRs targeting type-specific variant surface glycoprotein genes, mitochondrial minicircles and maxicircles, minisatellite markers and the F1-ATP synthase γ subunit gene. Nine stocks corresponded to type A, two stocks were type B and three stocks represented mixed infections between A and B, but not hybrids. One T. evansi type A stock was completely akinetoplastic. Five stocks were adapted to in vitro culture and subjected to a drug sensitivity assay with melarsomine dihydrochloride, diminazene diaceturate, isometamidium chloride and suramin. In vitro adaptation induced some loss of kinetoplasts within 60 days. No correlation between drug sensitivity and absence of the kinetoplast was observed. Sequencing the full coding sequence of the F1-ATP synthase γ subunit revealed new type-specific single nucleotide polymorphisms and deletions. CONCLUSIONS/SIGNIFICANCE:This study addresses some limitations of current molecular markers for T. evansi genotyping. Polymorphism within the F1-ATP synthase γ subunit gene may provide new markers to identify the T. evansi type that do not rely on variant surface glycoprotein genes or kinetoplast DNA.